Desarrollo de correlaciones para determinar el potencial a licuefacción aplicando el ensayo de penetración estática de piezocono (CPTu) en una cámara de calibración (CC) - Rodríguez-Rodríguez, Sebastián (Instituto Tecnológico de Costa Rica, 2018)
The main objective of this project was to develop correlations to determine the liquefaction potential of loose sand deposits, using the CPTu test; for this purpose, it was necessary to determine the behavior of CPTu tests in the calibration chamber (CC) of the Institute of Soil Mechanics and Rock Mechanics (IBF) in Karlsruhe Institute of Technology, moreoverto determine the resistance to liquefaction by means of cyclic undrained tests for sand samples, also to establish a correlation between the relative storage density (ID) of the sample, the tip resistance (qc) of the CPTu and the liquefaction resistance (CRR) of the triaxial tests and finally compare the experimental correlation obtained with existing correlations of the literature. With this project it was concluded that when comparing the correlations for the experimental materials studied by the IBF, it was determined that in the region of low storage densities and low peak resistances a good similarity. However, for higher densities and, therefore, greater peak resistances, the correlation curves for the experimental materials were flatter than in bibliographic references. In other words, the liquefaction resistance of the experimental materials in this area is lower than what the curves of the literature would have predicted. Finally, it is not possible to directly apply the results of this project in any other sand deposit; since the materials of the correlations made (Kali4) and other materials differ in aspects such as mineralogy (geological criteria), granulometry and particle form (composition criteria); which influence the susceptibility to liquefaction.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Densidad; Licuefacción; Resistencia; Arena; Calibración